Terapi Murotal dalam Upaya Meningkatkan Kualitas Tidur Lansia - Ricky Riyanto Iksan; Eni Hastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the analysis of marital therapy in the elderly, to provide an overview of mutual to improve the quality of sleep in the elderly, to find out the quality of sleep in the elderly before and after performing complementary therapy. The research design used is descriptive in the form of case studies. Results of research on subjects I and II can be seen differences in outcomes. Still, both of them experienced a decrease in the frequency of awakening and the duration of listening to mutual with the following results. Subject II experienced the sleep process of complementary therapy, which is faster by looking to shared 12 minutes 27 seconds. The subject can fall asleep while the subject I had a sleep process of 13 minutes 25 seconds. Conclusion, the aging process is a natural process accompanied by a decrease in the physical condition of the elderly, one of which is the change in the elderly's sleep Keywords: Al-Qur'an, Elderly Sleep Quality, Murottal Therapy